Does the Tendency for 'Quiet Quitting' Differ across Generations? Evidence from the UK - Odessa S. Hamilton; Daniel Jolles; Grace Lordan (Institute of Labor Economics (IZA), 2023)
The post-COVID-19 phenomenon of 'quiet quitting' could be problematic for UK economic growth because unpaid overtime has been a key contributor to business productivity since the 2008 global financial crisis. Here, we explore the extent to which this phenomenon exists in the UK, and whether the tendency for 'quiet quitting' differs across generations. We analysed data from the UK Quarterly Labour Force Survey (QLFS) between 2007-2022 to determine changes in hours worked. Quiet quitting was characterised by notable declines in hours worked between 2019-2022, benchmarked against 2007-2018 trajectories. Analyses were demarcated by four commonly defined generational cohorts (i.e., Generation Z [GenZs; 1997-2004], Generation Y [Millennials; 1981-1996], Generation X [GenXers; 1965-1980], and Baby Boomers [1952-1964]). Overall, we found that the UK workforce reduced hours by ~28 hours per year post-pandemic. Hours lost was most notable in 2022, with hours down by ~36 hours. However, in assessing generational differences, quiet quitting was most pronounced in the two younger cohorts. GenZs showed the steepest decline in hours worked, while Millennials worked the least number of hours overall, with no indication of recovery by the end of the study period. Hours declined for GenXers and Baby Boomers, but changes were more moderate, and Baby Boomers showed evidence of a possible rebound to pre-pandemic levels. Given the ~24,568 million UK full-time workers in 2022, our findings equate to over 55 million discretionary hours lost to the labour market per year between 2019-2022, 48.1% of which is accounted for by Millennials. Thus, we evidence that quiet quitting has interrupted the recovery of working hours in the UK to prepandemic levels, and lost hours are especially attributable to younger cohorts.
Keywords: J24; J01; 330; quiet quitting; generations